2012
DOI: 10.1111/j.1600-0501.2012.02518.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone loss biomarkers associated with peri‐implantitis. A cross‐sectional study

Abstract: The findings of this preliminary study on a relatively small sample size suggest that the PICF levels of biomarkers sRANKL, RANK, and OPG are associated with peri-implant tissue destruction and the pattern of these biomarkers differed when compared to periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 48 publications
(101 reference statements)
3
85
0
1
Order By: Relevance
“…Similar to findings in GCF obtained from sites with periodontitis (Belibasakis and Bostanci 2012), there is increasing evidence showing the association of the receptor activator of nuclear factor kappaB ligand (RANKL) -osteoprotegerin (OPG) system with the occurrence and severity of periimplantitis (Arikan et al 2008;Arikan et al 2011;Sarlati et al 2010;Guncu et al 2012;Duarte et al 2009a;Duarte et al 2009b;Rakic et al 2013). A few studies looking into other markers of bone metabolism, such as osteocalcin, reported that these are higher in PICF from peri-implant mucositis compared to healthy sites, whereas no differences were observed between periimplatitis and either mucositis or health.…”
mentioning
confidence: 73%
“…Similar to findings in GCF obtained from sites with periodontitis (Belibasakis and Bostanci 2012), there is increasing evidence showing the association of the receptor activator of nuclear factor kappaB ligand (RANKL) -osteoprotegerin (OPG) system with the occurrence and severity of periimplantitis (Arikan et al 2008;Arikan et al 2011;Sarlati et al 2010;Guncu et al 2012;Duarte et al 2009a;Duarte et al 2009b;Rakic et al 2013). A few studies looking into other markers of bone metabolism, such as osteocalcin, reported that these are higher in PICF from peri-implant mucositis compared to healthy sites, whereas no differences were observed between periimplatitis and either mucositis or health.…”
mentioning
confidence: 73%
“…Arikan et al [55] reported that sRANKL concentrations, OPG total amounts, and OPG concentrations were significantly lower in peri-implantitis group when compared to healthy group. In contrast, RANKL, RANK, and OPG concentrations were found to be significantly higher in peri-implantitis sites compared with healthy implant sites, but the ratio of OPG/RANKL was not different [56]. It was also demonstrated that the OPG/RANKL ratio improved with mechanical treatment of peri-implantitis sites [26].…”
Section: Discussionmentioning
confidence: 99%
“…Thus direct, indirect and synergic RANKL induced osteoclastogenesis play a role. Regarding the PICF levels, results are not consistent, and increased [63,64], lower [65] and similar [58,66] RANKL levels have been reported when comparing untreated diseased implants with healthy implants. However, the interpretation of these results cannot be dissociated from the overall RANKL/RANK/OPG system and the RANKL/OPG ratio, as the biological activity of RANKL is regulated by its decoy receptor OPG.…”
Section: Bone Cells Activity During Peri-implantitismentioning
confidence: 94%